2017
DOI: 10.1002/ejic.201700801
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of Trivalent Lanthanides with Bismalonamide Ligands: Implications for Liquid–Liquid Extraction

Abstract: The complexation of the bismalonamide ligand 2,2′-[1,2-phenylenebis(methylene)]bis(N,N,N′,N′-tetraethylmalonamide) (L), bearing two C-alkylated N,N,N′,N′-tetraethylmalonamide groups, onto an ortho-xylylene [C 6 H 4 (CH 2 ) 2 ] platform with trivalent lanthanides was investigated, both in solid and solution states. The crystal structures [Nd 2 (NO 3 ) 6 L 2 ]·(CH 3 CN) 3 (2), [Nd 2 (NO 3 ) 4 L 2 ]·[Nd(NO 3 ) 5 ]·(CH 3 CN) 1.5 (3), Ce(NO 3 ) 3 L 2 (4), and [NdL 2 ]·(ClO 4 ) 3 ·C 2 H 5 OH (5) were analyzed by sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…A valuable approach for the recovery of REEs is the use of multifunctional ligands, which can selectively separate lanthanide or actinide cations or a mixture of both. These ligands were specifically engineered to express different metal-to-ligand interaction geometries and strengths for a specific metal–ligand entity. In a slightly different approach, Bogart et al showed that dysprosium and neodymium preferentially formed monomeric and dimeric entities, respectively, when using a polydentate N′N3O3 donor ligand.…”
Section: Introductionmentioning
confidence: 99%
“…A valuable approach for the recovery of REEs is the use of multifunctional ligands, which can selectively separate lanthanide or actinide cations or a mixture of both. These ligands were specifically engineered to express different metal-to-ligand interaction geometries and strengths for a specific metal–ligand entity. In a slightly different approach, Bogart et al showed that dysprosium and neodymium preferentially formed monomeric and dimeric entities, respectively, when using a polydentate N′N3O3 donor ligand.…”
Section: Introductionmentioning
confidence: 99%